S30 Is the new national ltbi screening program reaching the target population? a population-based cohort study. (15th November 2017) - Berrocal-Almanza, LC; OConnell, AM; Muzyamba, MC; Mirza, A; Lalor, M; Lalvani, A; Zenner, D
Abstract : In England (73%) of TB cases occur among foreign-born individuals due to reactivation of Latent TB infection (LTBI). 1 The cornerstone of the global strategy to eliminate TB in low-incidence countries is to target preventative therapy at high-risk groups of developing active disease. England is the first country implementing a £10 m/annum program to systematically provide LTBI screening and treatment for new entrant migrants. 2 The main challenge is how to identify migrants eligible for screening among the reservoir of migrants already registered and those unregistered with primary-care. We aimed to establish the most feasible and effective method to localise migrants eligible for LTBI screening and to estimate population size, TB incidence after arrival and LTBI service utilisation of the target population. We performed a retrospective population based cohort study of VISA-applicants aged 16 to 35 years screened for active TB before entry to UK in 72 high-burden countries between 2011 and 2014. We used data record linkage of the pre-entry screening, the NHS Personal Demographic Service (PDS), the Enhanced TB Surveillance system and LTBI service utilisation databases. 1 93 979 migrants eligible for LTBI screening entered the UK between 2011 and 2014. A low proportion 78 395 (40.4%) registered in primary-care in the year of arrival, of whom 30 838 (39.3%) registered in high TB incidence areas of London and Midlands. We estimated the number of delayed registrations of the same age group in these areas by record linkage; 1 60 780 immigrants from the 72 high-burden countries registered between 2011 and 2014, of whom 1 29 942 (80.8%) arrived before 2011. These delayed registrants thus miss the window of opportunity for LTBI screening because the program targets arrivals within last five years. We estimated and compared TB incidence and LTBI service utilisation in the cohort of early vs delayed registrants. The program may be compromised by low and delayed primary-care registration, could be enhanced by promoting GP registration and community-based screening to reach unregistered migrants. References: Public Health England. Tuberculosis in England 2016. Public Health England. Collaborative Tuberculosis Strategy for England 2015–2020.